Kazakhstan : Background Paper and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This Background Paper and Statistical Appendix reviews the real economy and systemic reforms in the Republic of Kazakhstan during 1993-94. In early 1994, the Kazakh authorities launched a major stabilization program to improve the financial situation and reinforce the structural reforms. A tight budgetary stance was targeted, monetary policies were reinforced, and the liberalization of prices and the external trade regime continued. By the third quarter of 1994, inflation had been sharply reduced, the exchange rate had remained relatively stable for several months, and external reserves continued to rise.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet